Scheduling as a part of School Management System - Al-Hilali, Z. S. H. (Київський національний університет імені Тараса Шевченка, 2019)
Learning Management Systems are very popular nowadays. They have many functions to support the learning process, classes home assignments, communications, and progress tracking. However, it lacks the functionality for the management staff like scheduling (planning) and reporting. Here we propose the software solution, which solves this issue and provides the scheduling for the classes in a school or university, considering requirements, limitations, and wishes. An innovative approach was applied to the scheduling problem. This solution is based on the workforce management techniques known previously. The first positive feedbacks from Iraq schools, where we implemented this solution, support us for the next development and improvements of the system.The focus of the paper is the scheduling module of the system developed, the context of the task (the scope), and arguing why it is important. The method from the area of workforce management systems was taken, adopted, and applied to the new task of school scheduling construction. This is the novelty of the presented work.Key words: ---Pages of the article in the issue: 77 - 81Language of the article: Ukrainian